Low birthweight and risk of albuminuria in living kidney donors. (19th February 2014) - Berglund, Danielle; MacDonald, David; Jackson, Scott; Spong, Richard; Issa, Naim; Kukla, Aleksandra; Reule, Scott; Weber, Marc; Matas, Arthur J.; Ibrahim, Hassan N.
Abstract Low birthweight is linked to hypertension, chronic kidney disease and even end‐stage renal disease. We hypothesized that living kidney donors born with lower birthweight may be at increased risk of hypertension, albuminuria, or reduced GFR beyond what is typical following uninephrectomy. Two hundred fifty‐seven living kidney donors who donated at the University of Minnesota between 1967 and 2005 underwent iohexol GFR and urinary albumin excretion measurements. Predictors of iohexol GFR <60 mL/min/1.73 m2, albuminuria, and hypertension were examined using logistic regression. Predictors examined include age at GFR measurement, time since donation, BMI, gender, serum creatinine level (at donation and GFR measurement), systolic and diastolic blood pressure, race, and birthweight. The latter was obtained through self‐report and verified through birth certificates and family members. Older age, higher BMI, and time from donation were associated with reduced GFR. Older age and higher BMI were also associated with hypertension. Birthweight was not associated with GFR <60 mL/min/1.73 m2: OR=0.70, 95% CI (0.28, 1.74), p = 0.45 or hypertension: OR=0.92, 95% CI (0.46, 1.84), p = 0.82 but was associated with albuminuria: OR=0.37, 95% CI (0.15, 0.92), p = 0.03. These data further strengthen the link between low birthweight and potential adverse renal outcomes.